Tributação ambiental e a construção de uma nova sociabilidade:efetivando o direito fundamental ao meio ambiente ecologicamente equilibrado - Gomes, Marianna de Queiroz (2015)
From an exploratory research, draws up a panorama of the environmental crisis as a result of the depletion of the current development model. Contextualizes the environmental issue from the Gaia theory and paradigms of risk society and society's disappointment, from Beck and Lipovetsky. Discusses the fundamentals of environmental problems: lack of natural resources; increasing demand for environmental goods; development model that does not distribute income; compromising the ability of nature to provide future generations. Relates sustainable development and the consequent need for paradigm shift in human-environment relationship. Establishes the fundamental right to an ecologically balanced environment within the theory of fundamental rights and duties. Links the environment and human dignity. Studies the standards that prescribe in law the fundamental right to the environment. Reports on social and environmental responsibility prescribed by the Constitution. Relates taxation, tax induction, externalities and extrafiscality. Clarifies concepts, principles and possibilities of environmental taxation. Analyzes, from practical models, such as environmental taxation can promote values and carry out the fundamental right to an ecologically balanced environment and thereby assist in the implementation of sustainable development. Evaluates critical environmental taxation: its viability as public policy, the possible transfer of onus in dealing with environmental problems, membership in the Neoclassical Economics, its relationship to the state interventionism and solidarization of the economy. Ponders the guiding discourse of green taxation. Concludes the feasibility of environmental taxation as a mean of effecting the fundamental right to an healthy environment, linked to the evolution to a Environmental State and economical solidarization.